COST AND OPTIMIZATION IN GOVERNMENT an introduction to cost accounting, operations... management, and quality control. - Khan, Aman ([S.l.] : ROUTLEDGE, 2022)
The careful management of costs and operations are two of the most essential elements for successful operation of any organization - public, private, or nonprofit. This book demonstrates that a good grounding in cost basics, especially those related to cost accounting, operations management, and quality control can help all organizations, in particular government, increase efficiency, improve performance, and, in the end, do a better job of running its everyday operation. The book is divided into three parts: Part I offers thorough coverage of cost fundamentals, with an emphasis on basic cost concepts, cost behavior, cost analysis, cost assignment, cost allocation, and cost control. Part II deals with optimization in government. Included in this part are traditional or classical optimization with applications in inventory management and queuing, followed by mathematical programming, network analysis, productivity measurement, and games and decisions. Finally, Part III deals with a special case in cost and optimization that has become important in recent years - quality control. Simple, accessible language and explanations are integrated throughout, and examples have been drawn from government so that readers can easily relate to them. Cost and Optimization is required reading for practicing public managers and students of public administration in need of a clear, concise guide to efficient use of public resources.
OCLC-licensed vendor bibliographic record.
Keywords: POLITICAL SCIENCE / Public Affairs & Administration; POLITICAL SCIENCE / Government / General; Government productivity; Public administration -- Cost control; Public administration -- Cost effectiveness; Mathematical optimization